2015
DOI: 10.3945/jn.115.213736
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Practices among Poor Women in Mesoamerica

Abstract: Our study revealed significant variation in the prevalence of breastfeeding practices by poor women across countries surveyed by the Salud Mesoamérica 2015 initiative. Future interventions to promote exclusive breastfeeding should consider ways to leverage the role of the community in supporting individual women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
8
1
3
Order By: Relevance
“…This finding was similar with cross-sectional study reports [23, 24], but higher than other studies finding in Ethiopia of 52.4–63% [9, 25]. On the other hand, it was lower than the prevalence rate in rural central Ethiopia 92% [25], India 97.5% [26] and Panama 89.8v% [27]. …”
Section: Discussionsupporting
confidence: 89%
“…This finding was similar with cross-sectional study reports [23, 24], but higher than other studies finding in Ethiopia of 52.4–63% [9, 25]. On the other hand, it was lower than the prevalence rate in rural central Ethiopia 92% [25], India 97.5% [26] and Panama 89.8v% [27]. …”
Section: Discussionsupporting
confidence: 89%
“…The most common breastfeeding barriers reported in this study were family or friends as well as medical professionals encouraging formula supplementation and mothers having insufficient time to breastfeed. In contrast to other studies in Nicaragua and Latin America no demographic factors nor reporting insufficient time to breastfeed or insufficient breastmilk supply were found to correlate with early cessation of breastfeeding [5,7]. Surprisingly, more mothers who exclusively breastfed reported pain than those who discontinued earlier also in contrast to previous studies [6,17].…”
Section: Discussionmentioning
confidence: 59%
“…In contrast, a lower socioeconomic status, living in the central region, and female sex of the child were significantly correlated with increased rates of exclusive breastfeeding in Nicaragua [5]. A 2015 survey of mothers in Central America demonstrated that initiation of breastfeeding within 1 hour of life and mothers with at least a primary education were associated with increased rates of breastfeeding [7]. These factors have largely been addressed by the Baby Friendly Hospital initiative that has sought to embed a culture within birthing hospitals where early exclusive breastfeeding is both supported and encouraged [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Nicaragua, breastfeeding is highly prevalent (approximately 97%) during the first 6 months of life, therefore breastfed children could be either protected by maternal norovirus IgA or virus decoying human milk oligosaccharides [Colombara et al, 2015; Khodayar-Pardo et al, 2014; Weichert et al, 2016]. After weaning, children might both be more exposed to norovirus infections, and have less protection, factors that might explain the high GII.4 burden in that age group.…”
Section: Discusionmentioning
confidence: 99%